Improvements in posttransplant outcomes over two decades in older patients with acute myeloid leukemia in the EBMT ALWP study - Bazarbachi, Ali; Labopin, Myriam; Moukalled, Nour; Kröger, Nicolaus; Rautenberg, Christina; Schetelig, Johannes; Finke, Jürgen; Blau, Igor-Wolfgang; Blaise, Didier; Stelljes, Matthias; Eder, Matthias; Platzbecker, Uwe; et al. (Clinical cancer research, 2024)
Acute myeloid leukemia (AML) is a disease of older patients. Progress in allogeneic hematopoietic cell transplantation (allo-HCT) allowed the delivery of allo-HCT to older patients. We assessed changes over time in transplant characteristics and outcomes in patients with AML ages 65 years and above.We identified 7,215 patients with AML (median age 68 years, range 65-80) allografted between 2000 and 2021 in first complete remission (CR1; 64%), second or subsequent remission (CR2+; 14%), or active disease (22%).Median follow-up was 40 months. The 3-year cumulative relapse incidence (RI) gradually and significantly decreased from 37% to 31%, then to 30% (P = 0.001) over the three time periods (2000-2009; 2010-2014; 2015-2021), whereas nonrelapse mortality (NRM) decreased from 31% and 31% to 27% (P = 0.003). The 3-year leukemia-free survival (LFS) and overall survival (OS) gradually and significantly improved from 32% to 38%, and then to 44% (P = 0.001) and from 37% to 42%, and then to 49% (P = 0.001), respectively. In multivariate analysis, significant improvement in the RI, LFS, and OS were noted after 2015, whereas NRM was not significantly affected. This improvement was observed regardless of disease status at transplant.In older patients with AML, we observed an impressive improvement over time in posttransplant outcomes, mostly attributed to decreased RI rather than decreased NRM, and regardless of disease status at transplant. These large-scale, real-world data can serve as a benchmark for future studies in this setting and indicate that the opportunity for transplant for the elderly should be mandatory and no longer an option.